Nguplik: Women's Strategy Leaving the Domestic Sphere - Maulana, Moh. Faiz; Hafidzah, Laily (IAIN Pekalongan, 2021)
This paper highlights the strategies and efforts of Paciran women in the productive sphere. Even though women have played an important role in the economic life of the household, in fact, they still bear double burdens, they are still burdened and given household responsibilities. This is of course caused by the domination of patriarchal culture which is rooted in society. Women are considered as others who have boundaries, norms, and subordination of women to men in their environment. As a result, the strategy for selecting women's jobs that places the house as the main place is a real effort to reduce the domination of patriarchal culture. This research was conducted on women who work in Nguplik in a village in Paciran District, Lamongan Regency, East Java. Nguplik is the work of separating the shells or skins of cooked crabs from the meat to be sold and processed into food and cosmetics. Nguplik is carried out by individuals and or groups of women. This study uses a qualitative method with a gender anthropological approach, with the data collection process using in-depth interviews and observations. The finding of this study is the acceptance of women as workers.